Relationships between Maternal Beliefs and Reactions to Children's Negative Emotions - Filho, Nilton Correia dos Anjos (2022)
This study investigated relationships between maternal beliefs and responses to children’s negative emotions. Thirty-three mothers with children aged between 6 and 7 completed the Parents’ Beliefs about Children’s Emotions Questionnaire and the Coping with Children’s Negative Emotions Scale. The analyses revealed that beliefs in the cost of positivity concerning the potential harm of positive emotions explained 18% of the variance in non-supportive reactions to children’s expressions of negative emotions. Beliefs in the value of anger, regarding the recognition of its importance, explained 9% of the variance in supportive reactions to children’s emotional expressions. Maternal cognitions regarding the value of positive and negative emotions help explain the mothers’ behaviors toward children’s emotional expressions. Therefore, encouraging parents to understand the role of emotions in child development is essential to promote effective parenting practices.